Web based enterprise energy and building automation systems - Capehart, B. L.; Capehart, Lynne C. (Fairmont Press ; CRC Press : Distributed by Taylor & Francis, 2007)
Annotation The capability and use of IT and web based energy information and control systems has expanded from single facilities to multiple facilities and organizations with buildings located throughout the world. This book answers the question of how to take the mass of available data and extract from it simple and useful information which can determine what actions to take to improve efficiency and productivity of commercial, institutional and industrial facilities. The book also provides insight into the areas of advanced applications for web based EIS and ECS systems, and the integration of IT/web based information and control systems with existing BAS systems.
Keywords: Buildings -- Mechanical equipment -- Automatic control.; Buildings -- Energy conservation -- Automation.; elektronické knihy; electronic books